A first step towards best practice recommendations for the design and statistical analyses of pragmatic clinical trials: A modified Delphi approach. Issue 12 (1st July 2022) - Palin, Victoria; Van Staa, Tjeerd P.; Steels, Stephanie; Troxel, Andrea B.; Groenwold, Rolf H. H.; MacDonald, Tom M.; Torgerson, David; Faries, Douglas; Mancini, Pierre; Ouwens, Mario; Frith, Lucy J.; Tsirtsonis, Kate; et al.
Abstract : Aim: Pragmatic clinical trials (PCTs) are randomized trials implemented through routine clinical practice, where design parameters of traditional randomized controlled trials are modified to increase generalizability. However, this may introduce statistical challenges. We aimed to identify these challenges and discuss possible solutions leading to best practice recommendations for the design and analysis of PCTs. Methods: A modified Delphi method was used to reach consensus among a panel of 11 experts in clinical trials and statistics. Statistical issues were identified in a focused literature review and aggregated with insights and possible solutions from experts collected through a series of survey iterations. Issues were ranked according to their importance. Results: Twenty‐seven articles were included and combined with experts' insight to generate a list of issues categorized into participants, recruiting sites, randomization, blinding and intervention, outcome (selection and measurement) and data analysis. Consensus was reached about the most important issues: risk of participants' attrition, heterogeneity of "usual care" across sites, absence of blinding, use of a subjective endpoint and data analysis aligned with the trial estimand. Potential issues should be anticipated and preferably be addressed in the trial protocol. The experts provided solutions regarding data collection and data analysis, which were considered of equal importance. Discussion: A set of important statistical issues in PCTs was identified and approaches were suggested to anticipate and/or minimize these through data analysis. Any impact of choosing a pragmatic design feature should be gauged in the light of the trial estimand.